Adapting to Climate Change : The Case of Rice in Indonesia - World Bank (World Bank, Washington, DC, 2012)
There is increasing interest in climate change issues in Indonesia particularly in the lead-up to the COP13 or Copenhagen meeting in Bali in December 2007 when there was renewed focus on Indonesia as the third largest emitter of greenhouse gases (GHG) in the world due to deforestation, peat-land degradation, and forest fires. In Indonesia, the agriculture sector employs the largest share, 45 percent, of Indonesia's labor and contributes the second largest share, 17.5 percent, of gross domestic product (GDP). Poverty is a largely rural phenomenon. In 2002, 61 percent of the poor earned their livelihood in the agricultural sector while 63 percent of Indonesia's poor population resided in rural areas. In Indonesia, the agriculture sector is the main source of methane emissions as it accounts for 59 percent of total national emissions. Seventy percent of the emissions from the agriculture sector are generated by rice cultivation. Methane emission in agriculture is mainly due to inefficient practices such as over-irrigation, misuse of fertilizer, and poor livestock feeding practices. The study is organized as follows: the introductory chapter is followed by a chapter that discusses the key elements of adaptation in a general agricultural context. This is followed by a review of the literature on climate change in Indonesia and the implications for improving rice productivity in the context of concomitant changes in land use. Chapter four focuses on two key issues for economic and policy options as part of the adaptation agenda. The first relates to the important role of Bulog, (logistics agency) and the second pertains to the current structure of the fertilizer subsidies. The final chapter presents conclusions and recommendations.